2016
DOI: 10.1186/s40621-016-0093-4
|View full text |Cite
|
Sign up to set email alerts
|

Use, perceptions, and benefits of automotive technologies among aging drivers

Abstract: Advanced in-vehicle technologies have been proposed as a potential way to keep older adults driving for as long as they can safely do so, by taking into account the common declines in functional abilities experienced by older adults. The purpose of this report was to synthesize the knowledge about older drivers and advanced in-vehicle technologies, focusing on three areas: use (how older drivers use these technologies), perception (what they think about the technologies), and outcomes (the safety and/or comfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 116 publications
3
27
0
Order By: Relevance
“…Finally, the increase of vehicle-sharing services and the subsequent possible decrease of the requirements for construction of off-street parking spaces could increase housing affordability. Eby et al (2016) reported, in their review paper, a positive effect (i.e. avoiding crashes, enhancing easiness and comfort of driving, increasing place, and temporal accessibility) of many in-vehicle technologies (e.g.…”
Section: Assumptionsmentioning
confidence: 99%
“…Finally, the increase of vehicle-sharing services and the subsequent possible decrease of the requirements for construction of off-street parking spaces could increase housing affordability. Eby et al (2016) reported, in their review paper, a positive effect (i.e. avoiding crashes, enhancing easiness and comfort of driving, increasing place, and temporal accessibility) of many in-vehicle technologies (e.g.…”
Section: Assumptionsmentioning
confidence: 99%
“…Rather than converting directly to fully autonomous vehicles, consumers are being incrementally exposed to autonomous driving technologies within their existing cars in the form of various features including adaptive cruise control, lane keeping systems, automatic braking while skidding, parking assistance, and blind spot and collision warning systems (Eby et al, 2016;Payre et al, 2014;Richards & Stedmon, 2016). Drivers exhibit varying levels of awareness and use of these in-car technologies (Abraham et al, 2017), suggesting that it is important to also educate consumers about the benefits of these autonomous functions to increase their acceptance and use and provide opportunities for trial (Höltl & Trommer, 2013;Koo et al, 2015;Lee, Mehler, Reimer, & Coughlin, 2015;McDonald et al, 2016).…”
Section: General Approach To Communicationsmentioning
confidence: 99%
“…In fact, advanced in-vehicle technologies have already extended the period over which the elderly can drive safely and comfortably. Their full integration in AVs will lead to further improvement for all these sectors of society [104].…”
Section: Avs' Acceptabilitymentioning
confidence: 99%